Pengembangan “MICAYU”: Media Microsite untuk Proyek Prototype Free Energy Panel Surya dalam Pembelajaran Fisika Berbasis Proyek - Hidayah, Ifa; Asyhary, Fathya Zahra; Ilhamit Tamam, Ahmad Kevin (Inovasi: Jurnal Diklat Keagamaan, 2024)
Digital-based learning media is currently very popular with education practitioners. Apart from being a trend in the world of education, digital media is able to raise the enthusiasm of students to continue to be creative and innovate in presenting learning outcomes. In the independent curriculum, learning is expected to implement student-centered active learning models, one of which is project-based learning. The aim of this research is to describe the creation of project-based physics learning media with "MICAYU" media on alternative energy material and to determine the level of effectiveness of "MICAYU" as a media for showcasing physics learning projects. This research uses the ADDIE method (analysis, design, development, implementation and evaluation). This research produces a mini website that can be accessed anytime and anywhere. This mini web combines the Canva and YouTube applications to create a microsite that is packaged in a simple, interactive and attractive way. The research results show that the feasibility test from media experts and material experts is in the very high category with a percentage of 93.34%. From the results of the questionnaire analysis of student responses, it was found that 74% were in the practical category. Thus, MICAYU media is effectively used in project-based learning.